Clinical Study of Anlotinib as Third-Line or Above Therapy in Patients With Advanced or Metastatic Gastric Cancer: A Multicenter Retrospective Study - Nie, Caiyun; He, Yunduan; Lv, Huifang; Gao, Ming; Gao, Xiaohui; Chen, Beibei; Xu, Weifeng; Wang, Jianzheng; Liu, Yingjun; Zhao, Jing; Chen, Xiaobing (Frontiers in Oncology, 2022)
Background The present study was conducted to evaluate the efficacy and safety of anlotinib as third-line or above therapy for patients with advanced or metastatic gastric cancer. Methods Patients with advanced or metastatic gastric cancer who have failed from second-line treatment and treated with anlotinib monotherapy or combined with chemotherapy or immunotherapy from June 2019 to January 2021 in 3 institutions across China were retrospectively analyzed. The primary end point was progression free survival (PFS). Secondary end points included overall survival (OS), objective response rate (ORR), disease control rate (DCR), and safety. Results 43 patients with advanced or metastatic gastric cancer who have failed prior treatment received anlotinib monotherapy or combination therapy as third-line or above therapy. In the general population, 4 patients achieved PR, 21 patients had SD and 18 patients had PD. The overall ORR and DCR were 9.3% (4/43) and 58.1% (25/43), respectively. Median PFS and OS were 3.0 months (95% CI=2.5-3.5) and 6.0 months (95% CI=4.4-7.6), respectively. The incidence of Grade 3-4 adverse events(AEs) was 34.9%. Subgroup analysis suggested that the ORR of anlotinib combination therapy was superior than anlotinib monotherapy, but with similar PFS and OS. The clinical benefit of anlotinib was not associated with previously anti-angiogenesis therapy with apatinib. Conclusions Anlotinib monotherapy or combination therapy provide a feasible third-line or above therapeutic strategy in patients with advanced or metastatic gastric cancer a median PFS of 3.0 months and median OS of 6.0 months was obtained with well tolerated toxicity.